2017
DOI: 10.3847/2041-8213/aa72a2
|View full text |Cite
|
Sign up to set email alerts
|

Mixing and Transport of Dust in the Early Solar Nebula as Inferred from Titanium Isotope Variations among Chondrules

Abstract: Chondrules formed by the melting of dust aggregates in the solar protoplanetary disk and as such provide unique insights into how solid material was transported and mixed within the disk. Here Ti variations can be attributed to the addition of isotopically heterogeneous CAI-like material to enstatite and ordinary chondrite-like chondrule precursors. The new Ti isotopic data demonstrate that isotopic variations among carbonaceous chondrite chondrules do not require formation over a wide range of orbital dista… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
102
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(118 citation statements)
references
References 45 publications
15
102
1
Order By: Relevance
“…The Ti isotope anomalies in the CC chondrules are correlated with their Ti concentration and size, while no such relation is observed in OC and EC chondrules. This was interpreted as evidence for the presence and heterogeneous distribution of CAI-like material among chondrule precursors in the formation region of carbonaceous chondrites (Gerber et al 2017). These observations indicate that bulk carbonaceous chondrites do not only contain CAIs sensu stricto, but also reprocessed CAI-like material.…”
Section: Titanium Isotope Anomalies In Meteoritic Materialsmentioning
confidence: 96%
See 1 more Smart Citation
“…The Ti isotope anomalies in the CC chondrules are correlated with their Ti concentration and size, while no such relation is observed in OC and EC chondrules. This was interpreted as evidence for the presence and heterogeneous distribution of CAI-like material among chondrule precursors in the formation region of carbonaceous chondrites (Gerber et al 2017). These observations indicate that bulk carbonaceous chondrites do not only contain CAIs sensu stricto, but also reprocessed CAI-like material.…”
Section: Titanium Isotope Anomalies In Meteoritic Materialsmentioning
confidence: 96%
“…Chondrules from carbonaceous, ordinary, and enstatite chondrites (Gerber et al 2017), together with chondrite matrix, bulk meteorites, and CAIs (Trinquier et al 2009;Zhang et al 2011) plot along a single ε 46 Ti-ε 50 Ti correlation line ( Fig. 6b).…”
Section: Titanium Isotope Anomalies In Meteoritic Materialsmentioning
confidence: 99%
“…Indeed these CAIs are characterized by nucleosynthetic stable isotopic anomalies (e.g. in Ti, Ca; MacPherson 2014; Kööp et al 2018) much in excess of those seen in bulk chondrules (Gerber et al 2017) or meteorites (Trinquier et al 2009). This suggests they formed early, perhaps during infall of an isotopically heterogeneous protosolar cloud, before turbulent mixing essentially suppressed the heterogeneities (e.g.…”
Section: 2mentioning
confidence: 99%
“…There are however few such data on individual chondrules. Gerber et al (2017) found that the Ti isotope compositions of those chondrules were fairly uniform, around the terrestrial value, distinct from that of the (equally uniform) ordinary chondrite chondrules. This contrasts with the range exhibited in single carbonaceous chondrites, attributed by them to variable admixtures in their precursors of CAI-like material, presumably lacking in the enstatite chondrite reservoir.…”
Section: Isotopic Compositionmentioning
confidence: 84%